Public and Private Management: What’s the Difference? - Boyne, George A. (Journal of Management Studies, 2002)
Critics of New Public Management argue that differences between public and private organizations are so great that business practices should not be transferred to the public sector. In this paper the theoretical arguments on the differences between private firms and public agencies are reviewed, and 13 hypotheses are identified on the impact of publicness on organizational environments, goals, structures and managerial values. Evidence from 34 empirical studies of differences between public agencies and private firms is critically evaluated. Only three of the publicness hypotheses are supported by a majority of the empirical studies: public organizations are more bureaucratic, and public managers are less materialistic and have weaker organizational commitment than their private sector counterparts. However, most of the statistical evidence is derived from studies that use narrow measures of publicness and fail to control for other relevant explanatory variables. Whether the existing evidence understates or overstates the distinctiveness of public agencies is therefore unclear. A research agenda and methods are identified for better comparisons of management in public and private organizations.